ADP-ribosylation factor 1 dependent clathrin-coat assembly on synthetic liposomes - Zhu, Yunxiang (The National Academy of Sciences, 1999)
The assembly of clathrin-coated vesicles on Golgi membranes is initiated by the GTP-binding protein ADP ribosylation factor (ARF), which generates high-affinity membrane-binding sites for the heterotetrameric AP-1 adaptor complex. Once bound, the AP-1 recruits clathrin triskelia, which polymerize to form the coat. We have found that ARF⋅GTP also recruits AP-1 and clathrin onto protein-free liposomes. The efficiency of this process is modulated by the composition of the liposomes, with phosphatidylserine being the most stimulatory phospholipid. There is also a requirement for cytosolic factor(s) other than ARF. Thin-section electron microscopy shows the presence of clathrin-coated buds and vesicles that resemble those formed in vivo. These results indicate that AP-1-containing clathrin-coated vesicles can form in the absence of integral membrane proteins. Thus, ARF⋅GTP, appropriate lipids, and cytosolic factor(s) are the minimal components necessary for AP-1 clathrin-coat assembly.